Secret and power in social life - Labourdette, Sergio (2005)
Secret and power constitute two fundamental instances of the social world. Secret takes care of the concealment of things and of social processes. Secret is also a power device. Power is the social capacity to do, create, not doing and stop from doing. Secret and power get mutual feedback. Power uses the secret to protect his potential, be it what may, to increment its operative strength. Secret uses the power to achieve its aims and proposals. Social sciences seem to ignore the huge explanatory capacity of these two interrelated concepts, and even more, their powerful intervention in societies.